Traditional versus magnetically controlled growing rods for idiopathic early-onset scoliosis: outcomes at 5-year follow-up - Saarinen, Antti J.; Flynn, John M.; Thompson, George H.; Emans, John B.; Sturm, Peter F.; Sponseller, Paul D.; Helenius, Ilkka J.; Pediatric Spine Study Group (Elsevier BV, 2025)
Background context: Growing rods are the most common surgical treatment for EOS. However, in children with idiopathic EOS, it is unclear how clinical, radiographic, and HRQoL outcomes differ between those treated with MCGRs versus TGRs.
Purpose: To investigate how clinical, radiographic, and health-related quality-of-life (HRQoL) outcomes differ between children with idiopathic early-onset scoliosis (EOS) treated with magnetically controlled growing rods (MCGRs) versus traditional growing rods (TGRs).
Study design: A retrospective review.
Patient sample: Children with idiopathic EOS who have underwent treatment with MCGR.
Outcome measures: A disease-specific Early Onset Scoliosis Questionnaire 24, radiographic measurements, and complications.
Methods: Using an international database, we identified 92 children aged ≤9 years with idiopathic EOS (major curve >30°) treated with TGRs (n=54) or MCGRs (n=38) from 2002 to 2018. Mean age at index surgery was 6.4 years for both groups. The mean preoperative major coronal curve was 77° in the TGR group and 67° in the MCGR group (p=.04).
Results: At 5-year follow-up, mean (± standard deviation) major curves were 46°±18° in the TGR group and 38°±15° in the MCGR group (p=.03). Median annual thoracic growth (T1-T12) was 4.1 mm (interquartile range, 4.7 mm) in the TGR group and 3.2 mm (interquartile range, 5.6 mm) in the MCGR group (p=.29). More complications occurred in the TGR group (mean 2.1 per patient) than in the MCGR group (mean 1.0 per patient) (risk ratio, 2.1; 95% confidence interval: 1.3-3.2). More revisions occurred in the TGR group (2.0 per patient) than in the MCGR group (0.9 per patient) (risk ratio, 2.2; 95% confidence interval: 1.4-3.4). Both groups achieved maximum scores in HRQoL domains of pulmonary function, transfer, physical function, daily living, and financial impact; no other measured domains differed between groups.
Conclusions: The risks of complications and revision surgery in children with idiopathic EOS were lower for those treated with MCGRs than for those treated with TGRs. HRQoL scores were similar and high in both groups at 5-year follow-up. MCGRs provide safe, effective surgical treatment for idiopathic EOS.
Level of evidence: III.